From Behaviorism to New Behaviorism: A Review Study - Meisam Ziafar; Ehsan Namaziandost (English Education Department, 2019)
Neobehaviorism bridges the gap between behaviorism and cognitivism. Like Thorndike, Watson, and Pavlov, the neobehaviorists believe that the study of learning and a focus on rigorously objective observational methods are crucial to a scientific psychology. Unlike their predecessors, however, the neobehaviorists are more self-consciously attempting to formalize the laws of behavior. Neobehaviorism is associated with a number of scholars such as Tolman, Hull, Skinner, Hebb, and Bandura. Neobehaviorists demand formalizing the law of behavior. Neobehaviorism takes into consideration abstraction and hidden variables, it represents a holistic approach to behavior. It can be claimed that all neobehavioristic theories have been proposed in order to put some cognition within the mechanistic nature of traditional behaviorism.